2015
DOI: 10.1097/inf.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

No Survival Benefit With Empirical Vancomycin Therapy for Coagulase-negative Staphylococcal Bloodstream Infections in Infants

Abstract: Background Coagulase-negative Staphylococcus (CoNS) is the most common cause of bloodstream infections (BSI) in hospitalized infants. CoNS BSI is most reliably treated with vancomycin; however, concerns about side effects and promoting resistance often delay empirical vancomycin therapy until culture results become available. Methods All infants with CoNS BSI discharged from 348 neonatal intensive care units managed by the Pediatrix Medical Group from 1997–2012 were identified. Empirical vancomycin therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 34 publications
(32 reference statements)
1
16
0
1
Order By: Relevance
“…7 The mortality rate in the control group was threefold higher than the rates found in a recent study of 4364 infants with CoNS BSI. 19 Thus, it is possible that the benefit of a reduction in CoNS-mediated sepsis mortality associated with HRC monitoring may not translate to NICUs with typical CoNS mortality rates. Our data did not allow calculation of accurate predictive indices by episode of HRC elevation in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…7 The mortality rate in the control group was threefold higher than the rates found in a recent study of 4364 infants with CoNS BSI. 19 Thus, it is possible that the benefit of a reduction in CoNS-mediated sepsis mortality associated with HRC monitoring may not translate to NICUs with typical CoNS mortality rates. Our data did not allow calculation of accurate predictive indices by episode of HRC elevation in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…22 A similar study found that among neonates with LOS due to CoNS, vancomycin started on day 1 of therapy did not decrease the 30-day mortality rate compared with delayed vancomycin therapy started after blood culture results, although it did decrease the median duration of bacteremia by a day. 23 In our study, the most frequently isolated microorganism was CoNS, with the other isolated microorganisms being S. hominis, P. aeruginosa, and C. parapsilosis. Important pentoxifylline-associated adverse events are unusual.…”
Section: Discussionmentioning
confidence: 53%
“…7 The results of the SCOUT (Surveillance and Correction of Unnecessary Antibiotic Therapy) study determined culture-negative sepsis to be a large reason for the inappropriate continuation of antibiotic therapy, often 7 days or longer. 8 Another study by Ericson and colleagues 9 in 2015 strongly argued toward a new emphasis on the appropriate discontinuation of antibiotics in the NICU because of an increased risk of adverse effects as well as a lack of benefit for empiric vancomycin versus delayed start of vancomycin for the treatment of CONS bloodstream infections. The study showed an effective use of a restricted antibiotic policy to help prevent the inappropriate continuation of such drugs as vancomycin in the setting of late-onset sepsis in the NICU.…”
Section: Discussionmentioning
confidence: 99%